Development of Order Tracking and Mutation Check Modules in Rachmat Purnama Farm’s Chrysanthemum Tea E-Commerce - Dewi Renanti Medhanita; Ristianingrum Anita; Imas Faidoh Fatimah Ai; Lidya Leni (E3S Web of Conferences, 2023)
This research is focused on the design and implementation of an enhanced e-commerce system for Rachmat Purnama Farm’s Chrysanthemum Tea. It aims to improve the e-commerce system by introducing order tracking and automatic mutation check features. The research utilized the Extreme Programming (XP) approach for software development, along with observations, interviews with key stakeholders, and literature study. Through iterative design changes and thorough testing, the order tracking and automatic payment confirmation features were successfully integrated into the system. The research findings indicate a significant increase in online consumers, improved sales performance, and an expanded market reach. This research has demonstrated the benefits of incorporating innovative features into e-commerce systems to meet consumer demands and accelerate business growth.